Efficacy, safety, and immunogenicity of an inactivated, adjuvanted enterovirus 71 vaccine in infants and children: a multiregion, double-blind, randomised, placebo-controlled, phase 3 trial. Issue 10336 (30th April 2022) - Nguyen, Trong Toan; Chiu, Cheng-Hsun; Lin, Chien-Yu; Chiu, Nan-Chang; Chen, Po-Yen; Le, Thi Tuong Vy; Le, Dang Ngan; Duong, An Han; Nguyen, Van Luan; Huynh, Thi Nguyet; Truong, Huu Khanh; Phan, Trong Lan; et al.
Summary: Background: Children are susceptible to severe or fatal enterovirus 71 (EV71) infections. We aimed to evaluate the efficacy, safety, and immunogenicity of EV71vac, an aluminium phosphate-adjuvanted inactivated EV71 vaccine in children aged 2–71 months. Methods: We did a randomised, double-blinded, placebo-controlled, phase 3 trial at five hospitals in Taiwan and two in Vietnam. Children aged 2–71 months were stratified by country and age, and randomly assigned (1:1) to receive two doses of EV71vac or placebo via intramuscular injection 56 days apart. Children aged 2–23 months received a third booster dose on day 366. The primary endpoint was the clinical efficacy of the total vaccinated cohort against EV71-associated diseases during the follow-up period, from 14 days after the second dose to when 15 cases of EV71 infections were confirmed in the per-protocol population. Our safety analysis included all participants who received at least one dose of EV71vac. This trial is registered with ClinicalTrials.gov, NCT03865238, and is complete. Findings: Between April 23 and Dec 25, 2019, of 3663 children assessed, 3061 were randomly assigned, of whom 3049 were vaccinated: 1521 children in the EV71vac group and 1528 in the placebo group. By May 20, 2021, our primary efficacy analysis included 2959 children, with 1476 children in the EV71vac group and 1483 children in the placebo group. The vaccine efficacy of EV71vac was 96·8% (95% CI 85·5–100) against EV71 associated diseases (p<0·0001). The percentage of participants who reported solicited adverse events were similar in both groups: 865 (56·9%) in the EV71vac group and 852 (55·8%) in the placebo group. Almost all reported solicited adverse events were mild and self-limited. Interpretation: EV71vac is safe, well-tolerated, and highly effective in preventing EV71 associated diseases in children aged 2–71 months. Funding: Medigen Vaccine Biologics and A+ Industrial Innovative R&D Program of the Ministry of Economic Affairs, Taiwan.